Shea Butter (Vitellaria paradoxa) Biodiesel - Bello, Emmanuel I.; Mamman, A (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2015)
Shea butter was pretreated with sulphuric acid to convert the free fatty acids to esters and then transesterified to biodiesel using methanol and sodium hydroxide as catalyst. The oil, biodiesel, 10% and 20% blends with diesel were characterized according to ASTM and EN protocols for biodiesel. The fatty acid profile of the oil and biodiesel were analyzed using HP 6890 Gas Chromatography analyzer fitted with a flame ionization detector. From the results obtained, the properties of the biodiesel are by and large within the ASTM limits for biodiesel and the saturation to unsaturation ratio is 0.87 which gives a good balance of properties. The mineral contents are also within the ASTM limits for biodiesel. From the results obtained, it was concluded that the biodiesel can be used as alternative fuel for diesel engines.